AtTRB1–3 Mediates Structural Changes in AtPOT1b to Hold ssDNA. (16th February 2014) - Jaiswal, Amit
Abstract : POT from Arabidopsis thaliana is a member of shelterin complex and belongs to Telo_bind protein family. Three homologs are reported, namely, AtPOT1a, AtPOT1b, and AtPOT1c, where AtPOT1b is involved in genomic stability and chromosome end protection by providing necessary grip to G-rich region of telomeric DNA for telomerase assembly. Telomeric binding factors (TRB1–3) physically interact with POT with no known functionality. In this work attempt has been made to elucidate the reason behind the interaction by analyzing molecular docking interaction between AtPOT1b and AtTRB1–3, which yielded potential residues, which could play essential role in structural modification. 3 ns molecular simulation helped to look into structural stability and conformational dynamics portraying domain movements. AtTRB's interaction with AtPOT1b provoked structural changes in AtPOT1b, thereby increasing the affinity for single strand DNA (ssDNA) as compared to double strand DNA (dsDNA). Although the obtained results require experimental evidence they can act as a guide in tracing the functions in other organisms. The information provided in this paper would be helpful in understanding functions of TRB1–3 with respect to genomic stability.